Dixie Bohemia : A French Quarter Circle in the 1920s - Reed, John Shelton (Book collections on Project MUSE., 2012)
In the years following World War I, the New Orleans French Quarter attracted artists and writers with its low rents, faded charm, and colorful street life. By the 1920s, Jackson Square had become the center of a vibrant if short-lived bohemia. A young William Faulkner and his roommate William Spratling, an artist who taught at Tulane University, resided among the "artful and crafty ones of the French Quarter." In this book, the author introduces Faulkner's circle of friends - ranging from the distinguished Sherwood Anderson to a gender-bending Mardi Gras costume designer - and brings to life the people and places of New Orleans in the Jazz Age.